PLACE OF TRAVEL IN THE WORKS OF ABDULLAH AVLONI (Scientific journal of the Fergana State University, 2024)
The article reflects on the genre characteristics of the work "Afghan Travel" by Abdulla Avloni, a representative of Uzbek literature and a modern representative. Genre features of the work are analyzed.